2022
DOI: 10.1186/s13071-022-05259-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profiling of odorant receptor genes in the malaria vector Anopheles sinensis

Abstract: Background The olfactory system plays a crucial role in regulating insect behaviors. The detection of odorants is mainly mediated by various odorant receptors (ORs) that are expressed in the dendrites of olfactory neurons of chemosensilla. Anophelessinensis is a major malaria vector in Eastern Asia and its genome has recently been successfully sequenced and annotated. In this study, we present genome-wide identification and expression profiling of OR genes in different chemosensory tissues of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
1
4
0
Order By: Relevance
“…2A, D, E), whereas no uorescence was detected in any other tissues, including the proboscis and maxillary palps of both sexes (Fig. 2L-O), consistent with previous results (Qin et al 2014;He et al 2022). We did not detect GFP uorescence in the antennae of embryonic and pupal stages (Fig.…”
Section: Tissue-speci C Expression Of Asobp1 In Mosquito Antennaesupporting
confidence: 92%
See 3 more Smart Citations
“…2A, D, E), whereas no uorescence was detected in any other tissues, including the proboscis and maxillary palps of both sexes (Fig. 2L-O), consistent with previous results (Qin et al 2014;He et al 2022). We did not detect GFP uorescence in the antennae of embryonic and pupal stages (Fig.…”
Section: Tissue-speci C Expression Of Asobp1 In Mosquito Antennaesupporting
confidence: 92%
“…Our previous results showed that AsOBP1 is an antenna-speci c expression gene (Qin et al 2014;He et al 2022), which is corroborated by expression of AsOBP1 in a transgenic line of An. sinensis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…An empty engineered neuron of the Drosophila melanogaster was used as well to express mosquito olfactory-related genes and the responses of this neuron to individual odors were assayed using SSR [72]. Over the past decade, real-time qPCR, transcriptome based on RNA sequencing, and genome-wide analysis of the entire repertoire of olfactory-related genes were widely used to explore a comprehensive expression atlas specific to blood meal, sex, tissue and mosquito species, several olfactory-related genes associated with blood-seeking behavior in mosquitoes have been screened, and the functions in the behavior of which remain to be clarified one by one [73][74][75][76][77][78]. For Ae.…”
Section: Molecular Biology Studiesmentioning
confidence: 99%